2018
DOI: 10.7771/2327-2937.1109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tropical Climate on Selective Attention and Affect

Abstract: Heat has an impact on several aspects of human cognition but the effects of the tropical climate (i.e., hot and wet) have rarely been explored. The purpose of this study was to determine whether selective attention and affect are negatively impacted by the tropical climate. The study followed a within-participants design: participants responded to an affective scale (PANAS) and performed an attention task (d2 Test) in two experimental climate conditions (tropical vs. neutral) with a one-week interval between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Gaoua et al (2012) proposed that the subjective state of individuals is the main factor affecting task performance under conditions of heat stress. Our study showed that the athletes had significantly lower PA in TC than in AC and confirmed the results recently obtained by Coudevylle, Poparoch, Sinnapah, Hue, and Robin (2018) with students in tropical and neutral conditions. As PA is related to social activity, satisfaction, and the frequency of pleasant events (Watson et al, 1988), it may have been more pleasant for the athletes to be in AC than in TC, as confirmed by the results for thermal comfort.…”
Section: Environmental Perceptionsupporting
confidence: 92%
“…Gaoua et al (2012) proposed that the subjective state of individuals is the main factor affecting task performance under conditions of heat stress. Our study showed that the athletes had significantly lower PA in TC than in AC and confirmed the results recently obtained by Coudevylle, Poparoch, Sinnapah, Hue, and Robin (2018) with students in tropical and neutral conditions. As PA is related to social activity, satisfaction, and the frequency of pleasant events (Watson et al, 1988), it may have been more pleasant for the athletes to be in AC than in TC, as confirmed by the results for thermal comfort.…”
Section: Environmental Perceptionsupporting
confidence: 92%
“…We first postulated that MI ability would be negatively impacted at 11 a.m. and 2 p.m., due to environmental constraints (i.e., when temperatures are at their highest) compared to early morning (7 a.m.) and late afternoon (6 p.m.). Data supported this hypothesis as participants reached higher IVI and EVI scores and greater ability to achieve temporal congruence at 6 p.m. than at 11 a.m. and 2 p.m. As the respective mean temperatures were 26.4 °C, 30.2 °C, and 30.9 °C, data therefore confirmed the negative effect of heat stress on cognitive performance [33,43].…”
Section: Discussionsupporting
confidence: 52%
“…Affective states, as measured by the Positive and Negative Affect Schedule (PANAS; Watson et al, 1988) or the Feeling Scale (Hardy and Rejeski, 1989), may be another psychological markers for observing the impact of TC on athletes and determining whether or not intervention strategies are effective. While Gaoua et al (2012) showed that participants reported higher negative affect scores in a hot and dry environment than in neutral condition, other studies (Coudevylle et al, 2018;Robin et al, in press) showed that TC reduced positive affect scores without influencing negative affect. According to Acevedo and Ekkekakis (2001), the impact of the increase in the environmental temperature on psychological factors often precedes physiological deterioration.…”
Section: Consequences Of Tc For Affective Statesmentioning
confidence: 93%
“…Depending on their complexity, cognitive tasks may be differently impacted by TC ( Robin et al, in press ). Whereas heat stress does not affect tasks like simple tasks, more complex tasks such as a pointing task ( Ernwein and Keller, 1998 ; Robin et al, 2017 ) or sustained attention ( Vasmatzidis et al, 2002 ; Coudevylle et al, 2018 ) and working memory ( Gaoua et al, 2018 ) tasks are negatively affected. The effects of heat or TC on cognitive performance depend on multiple personal factors − such as level of expertise, sex, hydration status, and heat acclimation − and many external factors, including task duration, the methodology utilized to attain hyperthermia, and the intensity and duration of the thermal stressor (for a review, see Gaoua, 2010 ; Schmit et al, 2017 ).…”
Section: Psychological Impacts Of Tropical Climate On Athletes Duringmentioning
confidence: 99%